Arts, culture and the making of global cities creating new urban landscapes in Asia - Kong, Lily; Ching, Chia-ho; Chou, Tsu-Lung (Cheltenham, UK Edward Elgar Publishing, Inc., 2015)
This book is a welcome and timely analysis of how global economic and financial powerhouses in Asia also aim to become global cultural cities. It critically examines the tension between top-down policies implemented by strong states to boost urban culture, which are typically focused on the hardware of iconic venues, museums, and opera houses mostly designed by famous western architects, and the need for freedom to enable more organic cultural initiatives rooted in local practices.'--Robert C. Kloosterman, University of Amsterdam, the Netherlands. 'This book not only establishes the importance of cultural projects in crafting Asia's new global cities, it offers the first systematic comparison of both governmental plans and artists' actions in major urban sites from Beijing to Singapore. Whether art is viewed as an economic engine or a creative act, the authors show that it is a highly visible part of Asian societies that no one can ignore.'--Sharon Zukin, author of Naked City: The Death and Life of Authentic Urban Places. 'This volume makes two very significant contributions to the literature on Asian cities: it shifts the focus away from manufacturing and real estate as drivers of growth to the role of creativity in fostering the development of global cities; and it chronicles how arts and culture are changing the physical character of the cities studied. It is a highly welcome addition to our understanding of the dynamics of urban Asia and its increasing importance in generating global culture.'--Susan Fainstein, Harvard Graduate School of Design, US and author of The Just City. While global cities have mostly been characterized as sites of intensive and extensive economic activity, the quest for global city status also increasingly rests on the creative production and consumption of culture and the arts.
aArts, Culture and the Making of Global Cities examines such ambitions and projects undertaken in five major cities in Asia: Beijing, Shanghai, Taipei, Hong Kong and Singapore. Providing a thorough comparison of their urban imaging strategies and attempts to harness arts and culture, as well as more organically evolved arts activities and spaces, this book analyses the relative successes and failures of these cities. Offering rich ethnographic detail drawn from extensive fieldwork, the authors challenge city strategies and existing urban theories about cultural and creative clusters and reveal the many complexities in the art of city-making. This noteworthy study will appeal to undergraduate and graduate students, as well as academics from a variety of disciplines -ranging from urban and cultural geography to Asian studies. Arts and cultural policy makers and artists will also find this a fascinating read.
1. Arts spaces, new urban landscapes and global cultural cities -- 2. The National Grand Theatre in a city of monuments : discourse and reality in the construction of Beijing's new cultural space -- 3. Rivalling Beijing and the world : realizing Shanghai's ambitions through cultural infrastructure -- 4. Hong Kong's dilemmas and the changing fates of West Kowloon Cultural District -- 5. The making of a 'Renaissance City' : building cultural monuments in Singapore -- 6. In search of new homes : the absent new cultural monument in Taipei -- 7. Cultural creativity, clustering and the state in Beijing -- 8. Remaking Shanghai's old industrial spaces : the growth and growth of creative precincts -- 9. Factories and animal depots : the 'new' old spaces for the arts in Hong Kong -- 10. Reusing old factory spaces in Taipei : the challenges of developing cultural parks -- 11. From education to enterprise in Singapore : converting old schools to new artistic and aesthetic use -- 12. Culture, globalization and urban landscapes.
Includes bibliographical references (pages 225-249) and index.
Keywords: City planning -- Asia; Globalization